2019
DOI: 10.1007/s42729-019-00112-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations

Abstract: Drought is one of the major abiotic stresses to sustainable agriculture and global food security. The present study was conducted to evaluate the integrated effect of algal biochar (BC) and plant growth-promoting rhizobacteria (PGPR) on growth and physiology of maize under deficit irrigations. A pot experiment with different combinations of algal BC and PGPR under three deficit irrigations [field capacity (FC), 75% FC and 50% FC] was performed using maize as test crop. There were three controls without applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 42 publications
5
63
0
Order By: Relevance
“…It was clear from the data that drought stress had negative effects on the total dry weight of both cultivars, especially sensitive ones. This agreed with the results of Ullah et al (2020) who evidenced that all growth parameters such as plant height, leaf area, dry and fresh weight of root, and shoot fresh weight were significantly reduced under various deficit irrigations, whereas exogenous applications of both hormones under unstressed and stressed conditions improved these traits of this cultivar. Wang et al (2020) suggested that the application of JA to some plants might control the rate of photosynthesis by regulating the opening and closing of stomata.…”
Section: Discussionsupporting
confidence: 91%
“…It was clear from the data that drought stress had negative effects on the total dry weight of both cultivars, especially sensitive ones. This agreed with the results of Ullah et al (2020) who evidenced that all growth parameters such as plant height, leaf area, dry and fresh weight of root, and shoot fresh weight were significantly reduced under various deficit irrigations, whereas exogenous applications of both hormones under unstressed and stressed conditions improved these traits of this cultivar. Wang et al (2020) suggested that the application of JA to some plants might control the rate of photosynthesis by regulating the opening and closing of stomata.…”
Section: Discussionsupporting
confidence: 91%
“…However, to guarantee wheat production, the use of chemical fertilizers and pesticides is a common agronomic practice that is recognized to have negative effects on the environment and human health (Curtis and Halford 2014). In this context, the use of beneficial microorganisms (e.g., plant growth-promoting rhizobacteria [PGPR]) has emerged as an attractive alternative to ensure crop survival and maintain food security worldwide (Gouda et al 2018;Ullah et al 2019). Chile is not an exception, and native microorganisms also represent a biotechnological tool to guarantee wheat production.…”
Section: Introductionmentioning
confidence: 99%
“…This reduction is less in the case of turfs inoculated with Pf. In the same vein, Ullah et al (2019) also found that inoculation with PGPR increases P content of maize compared with control treatment under drought stress. P, as an essential macronutrient, has a special place in the growth and development of plants.…”
Section: Discussionmentioning
confidence: 68%
“…Therefore, by increasing root efficiency, the water efficiency by plants under stress is increased and results in an increase in TQ, FW, and RWC (Miransari 2014). For instance, as reported by Ullah et al (2019), PGPR significantly enhanced FW in maize under deficit irrigations compared with respective controls.…”
Section: Discussionmentioning
confidence: 74%